Cardiorenal syndrome. Prognostic value of renal biomarkers. Literature review - Nechai , Kateryna; Mostbauer , Halyna; Rudenko , Iuliia; Moskalenko , Yulia; Shevchuk , Mykhailo (The Ukrainian Scientific Medical Youth Journal, 2024)
cardiorenal syndrome includes a spectrum of disorders of the heart and kidneys, in which acute or chronic dysfunction of one organ can lead to the development of acute or chronic dysfunction of another organ. Changes in hemodynamics, activation of the renin-angiotensin-aldosterone system, metabolic disorders, inflammation, etc., are important in the pathogenesis of cardiorenal syndrome. The purpose of this article is to analyze and systematize the available contemporary scientific data on the role of renal biomarkers in stratifying the risk of development, mortality and repeated hospitalizations due to cardiorenal syndrome. Cardiorenal syndrome worsens the prognosis of patients, increases mortality, morbidity and the frequency of re-hospitalizations, therefore stratification of the risk of its development and early diagnosis are of great importance in order to timely prescribe treatment and improve the prognosis. Despite modern therapeutic treatment strategies, the mortality of patients with cardiorenal syndrome remains high. Serum creatinine still remains the "gold standard" for the diagnosis of kidney damage, although it is known as a low-sensitivity and unreliable biomarker, in particular, as is known, its concentration depends on gender, nutrition, muscle development, and tubular secretion. Taking into account these data, researchers and clinicians are making great efforts to find and study new biomarkers of acute kidney injury. Biomarkers of impaired function and integrity of kidney glomeruli include: serum creatinine, albuminuria, cystatin C, plasma proenkephalin A, galectin 3, and markers of impaired renal tubule integrity include: N-acetyl-beta-D-glucosaminidase, lipocalin, associated with neutrophil gelatinase, kidney damage molecule-1, etc. Literature data indicate that some of these new biomarkers are reliable predictors of the development of kidney damage and can be used to assess the prognosis of such patients.